A high throughput passive dosing format for the Fish Embryo Acute Toxicity test. (November 2015) - Vergauwen, Lucia; Schmidt, Stine N.; Stinckens, Evelyn; Maho, Walid; Blust, Ronny; Mayer, Philipp; Covaci, Adrian; Knapen, Dries
Graphical abstract: Highlights: Silicone O-rings are a practical means of applying passive dosing in the FET test. Controlled exposure conditions for phenanthrene were achieved. We report (sublethal) effect values in terms of chemical activity and body residue. Effect values were within ranges expected for baseline toxicity. Phenanthrene caused impaired swim bladder inflation and reduced motility. Abstract: High throughput testing according to the Fish Embryo Acute Toxicity (FET) test (OECD Testing Guideline 236) is usually conducted in well plates. In the case of hydrophobic test substances, sorptive and evaporative losses often result in declining and poorly controlled exposure conditions. Therefore, our objective was to improve exposure conditions in FET tests by evaluating a passive dosing format using silicone O-rings in standard 24-well polystyrene plates. We exposed zebrafish embryos to a series of phenanthrene concentrations until 120 h post fertilization (hpf), and obtained a linear dilution series. We report effect values for both mortality and sublethal morphological effects based on (1) measured exposure concentrations, (2) (lipid normalized) body residues and (3) chemical activity. The LC50 for 120 hpf was 310 μg/L, CBR50 (critical body residue) was 2.72 mmol/kg fresh wt and La50 (lethal chemical activity) was 0.047. All values were within ranges expected for baseline toxicity. Impaired swim bladder inflation was the most pronounced morphological effect and swimming activity was reduced in all exposure concentrations. Further analysis showed that the effect on swimming activity was not attributed to impaired swim bladder inflation, but rather to baseline toxicity. We conclude that silicone O-rings (1) produce a linear dilution series of phenanthrene in the 120 hpf FET test, (2) generate and maintain aqueous concentrations for reliable determination of effect concentrations, and allow for obtaining mechanistic toxicity information, and (3) cause no toxicity, demonstrating its potential as an extension of the FET test when testing hydrophobic chemicals.